2022
DOI: 10.1002/slct.202200549
|View full text |Cite
|
Sign up to set email alerts
|

Porous Silica Support for Immobilizing Chiral Metal Catalyst: Unravelling the Activity of Catalyst on Asymmetric Organic Transformations

Abstract: The role of chiral metal catalysts in asymmetric reactions has developed a new forte for researchers worldwide to boost chiral synthesis in various sectors. By controlling specific interactions among chiral ligands, metal catalysts and the support material, one can design a more selective and efficient chiral heterogeneous catalytic system. Silica has been extensively used as support material in various heterogeneous systems due to its activity, stability, better recovery, and recyclability. This review detail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 170 publications
0
6
0
Order By: Relevance
“…One of the most popular and important inorganic support materials used during the preparation of heterogeneous catalysts is the SiO 2 ‐based MCM‐41 and SBA‐15 materials 27–31 . These structures are called mesoporous silica nanoparticles (MSNs).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most popular and important inorganic support materials used during the preparation of heterogeneous catalysts is the SiO 2 ‐based MCM‐41 and SBA‐15 materials 27–31 . These structures are called mesoporous silica nanoparticles (MSNs).…”
Section: Introductionmentioning
confidence: 99%
“…One of the most popular and important inorganic support materials used during the preparation of heterogeneous catalysts is the SiO 2 -based MCM-41 and SBA-15 materials. [27][28][29][30][31] These structures are called mesoporous silica nanoparticles (MSNs). Functional MSNs obtained as a result of the functionalization of these materials with various groups have found many applications.…”
Section: Introductionmentioning
confidence: 99%
“…26,29 On the other hand, asymmetric catalysis in mesoporous solids is challenging, because various parameters such as pore size, pore polarity, lengths and flexibility of the linker between catalyst and pore wall, spatial distribution of the catalyst in the pores, surface modification or silanol groups remaining on the surface might interfere with the catalyst, substrate and/or products resulting in diffusion limitation, reduced reaction rates, unfavorable linker/catalyst, pore wall/ catalyst interactions or surface collapse ultimately leading to decreased yields and stereoselectivity. 22,25,[30][31][32][33] For example, in previous studies of the spacer type the influence of the length of unbranched alkyl linkers and ethylene glycol derived linkers on the activity of immobilized catalysts was compared. [34][35][36] It was found that longer linkers resulted in higher activity due to better flexibility and thus better accessibility of the catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…Just like non‐magnetic oxide NPs, the face of ferrite NPs is often modified by surfactants, silica, silicones, or phosphoric acid derivatives to increase their stability in solution. [ 10 ]…”
Section: Introductionmentioning
confidence: 99%
“…Just like non-magnetic oxide NPs, the face of ferrite NPs is often modified by surfactants, silica, silicones, or phosphoric acid derivatives to increase their stability in solution. [10] Transition metal complex, immobilized on magnetic solid supports, can be readily separated from the reaction batch using an external magnet, without the need for filtration, centrifugation, or other time-and energyconsuming processes. [4,5,11] Thus, one must come up with a strategy to carry out immobilization at its best.…”
Section: Introductionmentioning
confidence: 99%